The Expressive Language Skills of a Bilingual Child: A Case Study - Risnawati Risnawati; Nurnia Nurnia; Ader Laepe (Halu Oleo University, 2021)
This study attempted to explore the expressive language skills of a bilingual child from year to year. A qualitative method was used with the support of simple analysis of Mean Length Utterances calculation to answer the research question. The data was taken from the transcribed videos recorded intermittently from 2015 to 2020. Initially, the MLU score of the child was only 5.7 and it did not reach the standard score of6.88 for her age. However, the child’s MLU score for the following years rose even higher than it should be. The whole words of each utterance were counted then divided by the number of utterances. Based on the data, there was no significant improvement in 2019. This might be due to the fact that the data available in 2018 was of monologue type and that the subject was less willing to speak back then. Furthermore, based on the researcher’s observation, the English proficiency of the child, especially expressive language skills mastery, increased from year to year. Besides, the child was also shown to be more motivated. She kept practicing her English with her sister by watching and making English videos and acting as a professional YoutuberKeywords:The expressive language skills, Mean Length of Utterances, Bilingual child